Manajemen Perencanaan Tenaga Pendidik dan Kependidikan di Madrasah Tsanawiyah Al-Hidayah Pujud Kabupaten Rokan Hilir - Surya , Surya Subakti; M. Arif Surham; Tutti Adriani (Al-fahim : Jurnal Manajemen Pendidikan Islam, 2024)
The demands for an educator and educational staff are the demands of professional service users to provide educational services to students at educational institutions. The need for teaching staff and educational staff in providing educational services must meet certain requirements to ensure that the services needed are in line with the desired expectations. This requirement is very important because education providers demand professional expertise that not everyone can meet these requirements. This research uses qualitative analysis, data collection uses interviews and observation. Data sources consist of primary data sources obtained directly and secondary data sources. The results of the research show that: planning and analysis of the needs of Educators and Education Personnel includes: Recruitment, selection, placement, division of work tasks, workload, development, welfare, discipline and assessment, as well as dismissal of Educators and Education Personnel.